KARAKTERISTIK GANGGUAN NYERI SEBAGAI GEJALA NON-MOTORIK PADA PENYAKIT PARKINSON - Vincent Ongko Wijaya; Rizaldy Taslim Pinzon (NEURONA, 2018)
PAIN CHARACTERISTICS AS NON-MOTOR SYMPTOM IN PARKINSON DISEASEABSTRACTIntroduction: Parkinson’s Disease (PD) as a progressive neurodegenerative disorder of the central nervous system that has motor and non-motor symptom. Pain is one of the most common non-motor symptom of PD and has a significant impact in impairment of patients quality of life, therefore understanding the characteristics of pain in PD is needed.Aim: To obtain the characteristics of pain disorder in Parkinson’s Disease patients.Method: This was an observational descriptive study with cross sectional design in PD patients Bethesda Hospital in Yogyakarta from January to March 2018. The characteristics of pain in PD patients was assessed based on anamnesis and King’s Parkinson Disease Pain Scale (KPPS) questionnaire filling.Result: Thirty-one PD patients were assessed with majority being male (54.8%), >70 years old (45.15%), H&Y stage III (64.5%), and disease duration 1-2 years (41.9%). Pain was present in over 70.96% patients mostly musculoskeletal pain (45.2%), followed by nocturnal pain (25.8%) and radicular pain (25.8%).Discussion: The prevalence of pain as non-motor symptom of PD patients with majority in H&Y stage III was 70.96%, with the most common types were musculoskeletal pain, nocturnal pain, and radicular pain.Keywords: Pain, parkinson’s diseaseABSTRAKPendahuluan: Penyakit Parkinson (PP) adalah kelainan neurodegeneratif sistem saraf pusat (SSP) yang progresif dengan gejala motorik dan non-motorik. Nyeri merupakan salah satu manifestasi non-motorik tersering pada PP, serta berperan cukup signifikan terhadap penurunan kualitas hidup pada pasien, sehingga diperlukan pemahaman mengenai karakteristik nyeri pada PP.Tujuan: Mengetahui prevalensi dan karakteristik gangguan nyeri pada pasien PP.Metode: Penelitian deskriptif observasional secara potong lintang terhadap pasien PP di RS Bethesda, Yogyakarta, pada bulan Januari hingga Maret 2018. Karakteristik nyeri pada pasien PP dinilai berdasarkan hasil anamnesis melalui pengisian kuesioner King’s Parkinson Disease Pain Scale (KPPS).Hasil: Didapatkan 31 subjek PP yang mayoritas laki-laki (54,8%) berusia >70 tahun (45,1%), berada stadium III (64,5%), dan durasi sakit 1-2 tahun (41,9%). Nyeri ditemukan pada 70,96% subjek, berupa nyeri muskuloskeletal (45,2%), nyeri nokturnal (25,8%), dan nyeri radikuler (25,8%).Diskusi: Prevalensi nyeri sebagai gejala non-motorik pada PP yang mayoritas berada pada stadium III adalah 70,96% dengan karakteristik nyeri terbanyak berupa nyeri muskuloskeletal, nyeri nokturnal, dan nyeri radikular.Kata kunci:  Nyeri, penyakit Parkinson